Pertimbangan Hakim Pengadilan Agama Kelas IA Tanjung Karang Tentang Pembagian Harta Bersama Antara Suami dan Isteri - Meita Djohan Oelangan; . Kamsari (KEADILAN PROGRESIF, 2012)
Problem of community property is territory of jurisdiction whidh not touched or not thought (ghair al-mufakkar fih). Spouse of wife husband which have divorced even progressively noise with .Problem of community property which complicated, finally back part to progressively  make  conference hot in justice because both side claim even she/he which have rights to get bigger than his/her couple. But, time and social cortex in modern epoch now already different where with limitation and husband skill caused wife to not stay quite and follow to account family economy burden.  If happen  problem of community property must finished wih justice, consideration of judge with ½ : ½ feel not fair according to wife, so that arise a problem, how about consideration of judge in stop the dispute of community property and how about its solution. This research to analyzing considering of judge in comprehending section 97 KHI about divided dispute of community property. Method which used by passing Yuridis Empiris approach. Empiris approach because approach to get divide of community property data among wife and husband to give sense of justice to people. Result of research which get where judge in give considering and fairing just see with casuistis and tend to think doktriner-normatif-deduktif., though regulation about devide of community property  having character absolute. But according to judge to do ijtihad finding a new law to make the people feel fair. Example, if wife have contribution bigger than in community property, while husband is not work and have bad character hence the divide is not ½ : ½ but can other specified, example ¾ : ¼  ( wife get ¾ and husband get ¼, so the rights of wife is protected).